Blood flukes (Digenea: Aporocotylidae) of epipelagic lamniforms: Redescription of Hyperandrotrema cetorhini from Basking Shark (Cetorhinus maximus) and description of a new congener from Shortfin Mako Shark (Isurus oxyrinchus) off Alabama - Orélis-Ribeiro, R.; Ruiz, C. F.; Curran, S. S.; Bullard, S. A. (Journal of Parasitology, 2013)
We emend the original generic diagnosis for Hyperandrotrema Maillard and Ktari, 1978 , and redescribe its type species Hyperandrotrema cetorhini Maillard and Ktari, 1978 (Digenea: Aporocotylidae Odhner, 1912), based on the holotype and 2 paratypes collected from the heart of basking shark (Cetorhinus maximus). We also describe Hyperandrotrema walterboegeri Orélis-Ribeiro and Bullard n. sp. based on light and scanning electron microscopy of 6 adult specimens collected from the heart of a shortfin mako shark (Isurus oxyrinchus Rafinesque, 1810) captured from Viosca Knoll (29°11.70'N, 88°33.32'W; 123 km southwest of Dauphin Island, Alabama), northern Gulf of Mexico. Hyperandrotrema spp. infect lamniforms and differ from all other nominal aporocotylids at least by having a ventrolateral field of robust C-shaped spines (rather than transverse rows of minute, shaft-like spines), an inverse U-shaped intestine with extremely elongate ceca terminating near the level of the excretory bladder, and a common genital pore that comprises the dorsal opening of a common genital atrium. Adults of the new species exceeded 12 mm in total length, making them the largest of the nominal fish blood flukes. The new species further differs from H. cetorhini by the combination of having an adult body that is 7-8 times longer than wide, large midbody tegumental spines measuring 25-38 μm long × 10-12 μm wide, a long vas deferens 4-5% of the body length, a testis 9-11 times longer than wide, and a large ootype 105-150 μm long × 85-105 μm wide. This is the first report of Hyperandrotrema from the Gulf of Mexico and the second aporocotylid species reported from an epipelagic elasmobranch. Our results demonstrate that ecologically related (epipelagic, marine) and phylogenetically related (Lamniformes) definitive hosts are infected by morphologically similar (congeneric) fish blood flukes.